Risperidone long-acting injection (RLAI): The 12-week efficacy and tolerability in thai patients with chronic schizophrenia - Arunpongpaisal S. (2017)
Background: Although oral atypical antipsychotics have improved the outcomes in schizophrenia, the patient medication adherence plays role as the important factor to clinical potential of the drugs. Therefore, the long-acting formulations of antipsychotics have been developed to improve the treatment compliance in patient with schizophrenia and risperidone long-acting injection (RLAI) is the first long-acting injectable drug since then. Objective: To evaluate the efficacy and tolerability of long-acting risperidone injection in Thai patients with chronic schizophrenia for 12 weeks treatment. Material and Method: This was a non-randomized, open-label, single-arm study, performed at 5 centers in Thailand. The eligible patients with schizophrenia diagnosed by DSM-IV criteria were enrolled. Patients received long-acting risperidone injection 25, 37.5 or 50 mg every 2 weeks. Efficacy assessments were measured by Manchester Psychiatric Rating Scale (MPS), CGI-S and SF-36 at baseline, week 6 and week 12 or end point visit. Tolerability assessments were measured by Yale Extrapyramidal Symptoms Rating Scale (YESS), Visual analogue scale 10-cm for pain at injection site, body weight (BW) and incidence of adverse events. Results: Of 184 patients recruited, 160 patients (87%) completed the study. RLAI produced a significant improvement (p < 0.001) in MPS positive score from baseline to endpoint, 4.4 + 3.7 to 1.6 + 2.6. There was also significant reduction in MPS negative score, from 3.06 + 2.68 to 0.93 + 1.61 at endpoint (p < 0.001). The CGI-S score improved significantly from baseline to end point (p < 0.001), as reflected by the increase the proportion of patients rated as "not ill" or "borderline ill" from 5.9% at baseline to 53.2% at endpoint. Quality of life measured on the SF-36 scale was improved in all domains except bodily pain. Movement disorders, measured by YESS, were significantly reduced following RLAI introduction. Treatment with this drug was well tolerated and no significant weight gain occurred during the study. Conclusion: This study suggests that RLAI produces symptomatic improvement in chronic schizophrenia patients, along with improvement of movement disorders and had a good tolerability and adherence to treatment.